PENGARUH METODE SMALL GROUP DISCUSSION TERHADAP KETERAMPILAN BERBICARA SISWA KELAS V SD NEGERI MANNURUKI KOTA MAKASSAR - Sri Wahyu Nengsi; Aliem Bahri; Anin Asnidar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Sri Wahyu Nengsi. 2026. The Effect of the Small Group Discussion Method on the Speaking Skills of Fifth-Grade Students at the SPF Unit of Mannuruki Public Elementary School. Thesis. Department of Elementary School Teacher Education, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. Supervisor I Aliem Bahri and Supervisor II Anin Asnidar. This study aims to determine the effect of the Small Group Discussion method on the speaking skills of fifth-grade students at the SPF Unit of Mannuruki Public Elementary School, Makassar City. The background of this study is based on students' low speaking skills, characterized by a lack of courage in expressing opinions, low student participation during the learning process, and the use of learning methods that still do not actively involve students in learning activities. This study used a quantitative approach with an experimental research design using a One Group Pretest-Posttest Design. The sample in this study consisted of 30 fifth-grade students at the SPF Unit of Mannuruki Public Elementary School, Makassar City. The instruments used were a speaking skills test and an observation sheet. Data collection techniques were conducted through tests, observation, and documentation. Data analysis techniques used descriptive and inferential statistics with the assistance of IBM SPSS Statistics Version 26.The results showed that before the implementation of the Small Group Discussion method, the average pretest score for students was 37.1667, with a highest score of 47 and a lowest score of 28, indicating that all students were considered incomplete. After the implementation of the Small Group Discussion method, the average posttest score for students increased to 81.9333, with a highest score of 91 and a lowest score of 74, indicating that all students were considered incomplete. Furthermore, the results of the hypothesis test using the Paired Sample T-Test obtained a significance value of 0.000 <0.05, indicating a significant effect on students' speaking skills after the implementation of the Small Group Discussion method. Therefore, it can be concluded that the Small Group Discussion method has a significant effect on improving the speaking skills of fifth-grade students at the UPT SPF of Mannuruki Elementary School, Makassar City, in learning Indonesian.